2011
DOI: 10.1159/000333417
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Risk Factors and Sex Differences in Ischemic Stroke in the Ludwigshafen Stroke Study, a Population-Based Stroke Registry

Abstract: Background: Stroke etiology in ischemic stroke guides preventive measures and etiological stroke subgroups may show considerable differences between both sexes. In a population-based stroke registry we analyzed etiological subgroups of ischemic stroke and calculated sex-specific incidence and mortality rates. Methods: The Ludwigshafen Stroke Study is a prospective ongoing population-based stroke registry. Multiple overlapping methods of case ascertainment were used to identify all patients with incident stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
64
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 52 publications
11
64
4
1
Order By: Relevance
“…The aetiology of stroke is influenced by sex, race and age, as well as by cultural and geographic factors 1, 2, 3, 4, 5, 6. Stroke subtypes are commonly categorized as large‐artery atherosclerosis (LAA), cardioembolism (CE), small‐vessel occlusion (SVO), stroke of other determined cause (SOC) and stroke of undetermined cause (SUC) (TOAST criteria) 7.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of stroke is influenced by sex, race and age, as well as by cultural and geographic factors 1, 2, 3, 4, 5, 6. Stroke subtypes are commonly categorized as large‐artery atherosclerosis (LAA), cardioembolism (CE), small‐vessel occlusion (SVO), stroke of other determined cause (SOC) and stroke of undetermined cause (SUC) (TOAST criteria) 7.…”
Section: Introductionmentioning
confidence: 99%
“…The age-adjusted incidence of CE stroke ranges from 17 to 40 per 100,000 person-years 4,5 . As the prevalence of AF increases, due partly to the aging population 6 , we would expect more AF-related CE strokes in the future 7 .…”
mentioning
confidence: 99%
“…German Ludwigshafen Stroke Study evaluated 1,231 patients hospitalized due to ischaemic stroke or transient ischaemic attack (TIA). AF was newly detected in 36% of these patients [12]. In our study, all patients had resting ECG recorded on admission, and most patients underwent Holter monitoring.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, subjects above 74 years of age accounted for a particularly large proportion of patients with AF. Other authors also reported that patients with stroke and AF were older than those without arrhythmia [11,12].…”
Section: Discussionmentioning
confidence: 99%